From strategy to implementation: What is desirable and what realistic? - Henning Kroll (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2018)
[Introduction] In recent years, the debate on "policy mixes" (Howlett 2005; Borrás 2009; Flanagan et al. 2011) has (re)gained momentum. Increasingly it has moved beyond a development of instrument typologies and 'toolbox approaches' (Howlett 2011; Kroll 2016) to considerations of measures' roles in strategic frameworks and constellations of governance (Howlett and Rayner 2007; Lanzalaco 2011; Navarro et al. 2014; Magro and Wilson 2015). Furthermore, many recent contributions place additional emphasis on path dependencies and counteracting factors (Magro und Wilson 2013; Peters et al. 2018). In doing so, they align with existing literature on the reflexive emergence of political decisions (Edler et al. 2003; Smits et al. 2010; Edler and James 2015; Colebatch 2017; Kingdon 1984) as well as long-established findings on the complexity of policy learning and implementation (Lindblom 1959; Bennett and Howlett 1992; Howlett et al. 2015; Howlett et al. 2017). For the inevitable assessment of policies, this situation creates new challenges. Over the years, many limits to coordinated policy design have convincingly been discussed and demonstrated (Arnold 2004; Molas-Gallart and Davies 2006; Lascoumes and Le Galès 2007; Howlett 2009) but at times of challenge-driven and transformation oriented policy ambitions (Kuhlmann and Rip 2018; Schot and Kanger 2018) the incidence of strategically coordinated attempts at policy implementation is undoubtedly increasing. Despite a persistent and continuous flow of individual implementation decisions, more and more political strategies have become more than passive reflections of a debate's status quo at a certain point in time, making it problematic that a generally agreed on approach to assess them has yet to be established (Peters et al. 2018). [...]
urn:nbn:de:0011-n-5098707
Keywords: 330